The order [compact disc, unabridged] : a novel - Silva, Daniel, 1960- (Silva, Daniel, 1960- Gabriel Allon series., 2020)
Gabriel Allon is called to investigate the death of Pope Paul VII, as some insiders believe the death was actually a murder after the pope found a long-suppressed gospel in the Vatican secret archives.